A method for the precise measurement of the difference between two low frequencies - Kasparis, Takis; Voulgaris, Nicholas C.; Halkias, Christos C. (My University, 1985)
A method is presented for measuring the difference between two low frequencies with high resolution. The method is based on multiplying the two incoming frequencies by a large factor and then using a BCD up/down counter to store and display the resulting frequency difference.
Keywords: Electronic circuits; Counting; Signal processing; Electric measurements